The Relevance of an Existential Conception of Nature - Mei, Todd (Cosmos and History: The Journal of Natural and Social Philosophy, 2014)
<!–[if gte mso 9]> <![endif]–> It is often assumed that science provides the most accurate knowledge about nature. This view not only collapses distinctions between different forms of knowing but also results in a paradox whereby understanding what it means to exist in the world is dictated by practioners of science. In this essay I argue for the relevance of an existential conception of nature via the philosophy of Martin Heidegger, and how his notions of thrownness and phusis enable us to recognize a certain ethical bond to nature. I conclude with a critical analysis of liability insurance and actuarial science to demonstrate my points. <!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>